Interventions for protecting renal function in the perioperative period - Zacharias, Mathew; Mugawar, Mohan; Herbison, G Peter; Walker, Robert J; Hovhannisyan, Karen; Sivalingam, Pal; Conlon, Niamh P (Cochrane database of systematic reviews, 2013)
Various methods have been used to try to protect kidney function in patients undergoing surgery. These most often include pharmacological interventions such as dopamine and its analogues, diuretics, calcium channel blockers, angiotensin-converting enzyme (ACE) inhibitors, N-acetyl cysteine (NAC), atrial natriuretic peptide (ANP), sodium bicarbonate, antioxidants and erythropoietin (EPO). This review is aimed at determining the effectiveness of various measures advocated to protect patients' kidneys during the perioperative period.We considered the following questions: (1) Are any specific measures known to protect kidney function during the perioperative period? (2) Of measures used to protect the kidneys during the perioperative period, does any one method appear to be more effective than the others? (3) Of measures used to protect the kidneys during the perioperative period,does any one method appear to be safer than the others? In this updated review, we searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, Issue 2, 2012), MEDLINE (Ovid SP) (1966 to August 2012) and EMBASE (Ovid SP) (1988 to August 2012). We originally handsearched six journals (Anesthesia and Analgesia, Anesthesiology, Annals of Surgery, British Journal of Anaesthesia, Journal of Thoracic and Cardiovascular Surgery, and Journal of Vascular Surgery) (1985 to 2004). However, because these journals are properly indexed in MEDLINE, we decided to rely on electronic searches only without handsearching the journals from 2004 onwards. We selected all randomized controlled trials in adults undergoing surgery for which a treatment measure was used for the purpose of providing renal protection during the perioperative period. We selected 72 studies for inclusion in this review. Two review authors extracted data from all selected studies and entered them into RevMan 5.1; then the data were appropriately analysed. We performed subgroup analyses for type of intervention, type of surgical procedure and pre-existing renal dysfunction. We undertook sensitivity analyses for studies with high and moderately good methodological quality. The updated review included data from 72 studies, comprising a total of 4378 participants. Of these, 2291 received some form of treatment and 2087 acted as controls. The interventions consisted most often of different pharmaceutical agents, such as dopamine and its analogues, diuretics, calcium channel blockers, ACE inhibitors, NAC, ANP, sodium bicarbonate, antioxidants and EPO or selected hydration fluids. Some clinical heterogeneity and varying risk of bias were noted amongst the studies, although we were able to meaningfully interpret the data. Results showed significant heterogeneity and indicated that most interventions provided no benefit.Data on perioperative mortality were reported in 41 studies and data on acute renal injury in 44 studies (all interventions combined). Because of considerable clinical heterogeneity (different clinical scenarios, as well as considerable methodological variability amongst the studies), we did not perform a meta-analysis on the combined data.Subgroup analysis of major interventions and surgical procedures showed no significant influence of interventions on reported mortality and acute renal injury. For the subgroup of participants who had pre-existing renal damage, the risk of mortality from 10 trials (959 participants) was estimated as odds ratio (OR) 0.76, 95% confidence interval (CI) 0.38 to 1.52; the risk of acute renal injury (as reported in the trials) was estimated from 11 trials (979 participants) as OR 0.43, 95% CI 0.23 to 0.80. Subgroup analysis of studies that were rated as having low risk of bias revealed that 19 studies reported mortality numbers (1604 participants); OR was 1.01, 95% CI 0.54 to 1.90. Fifteen studies reported data on acute renal injury (criteria chosen by the individual studies; 1600 participants); OR was 1.03, 95% CI 0.54 to 1.97. No reliable evidence from the available literature suggests that interventions during surgery can protect the kidneys from damage. However, the criteria used to diagnose acute renal damage varied in many of the older studies selected for inclusion in this review, many of which suffered from poor methodological quality such as insufficient participant numbers and poor definitions of end points such as acute renal failure and acute renal injury. Recent methods of detecting renal damage such as the use of specific biomarkers and better defined criteria for identifying renal damage (RIFLE (risk, injury, failure, loss of kidney function and end-stage renal failure) or AKI (acute kidney injury)) may have to be explored further to determine any possible benefit derived from interventions used to protect the kidneys during the perioperative period.